Synthesis of gem-difluoromethylenated bicyclo[ m.n. 0]alkan-1-ols and their ring-expansion to gem-difluoromethylenated macrocyclic lactones - Teerachai Punirun (2018)
Fluoride-catalyzed stereoselective nucleophilic addition of PhSCF 2 SiMe 3 (1) to α-carboethoxycycloalkanones 2 followed by intramolecular radical cyclization of the resulting cis-3 adduct afforded the corresponding gem-difluoromethylenated bicyclic compounds 4, which underwent ring-expansion followed by the Baeyer-Villiger-type oxidation of the resulting macrocyclic ketone intermediates to give gem-difluoromethylenated macrocyclic lactones 5. © 2012 American Chemical Society.